Aksiologi Rekonstruksi Pendidikan Islam Perspektif Al Syaibani - Mamdukh Budiman (Universitas Al-Amien Prenduan, 2018)
Education is a system, observing and reviewing the education is the same as observing a tangled thread, because the education is a system, a unit consisting of interrelated components or elements. These problems will be answered in a philosophical foundation that is able to describe the problem, Educational Axiology aims to pass down values that are considered important for the development of one's personality. Implications and values (axiology) in education must be integrated as a whole. An integrated constructionism, harmonization of western and Islamic ethics and aesthetics: an offer. This study uses a type of library research, which is a series of activities related to the methods of collecting library data, reading and taking notes and processing research materials.